Language Manipulation in Tourism Promotion: A Forensic Psycholinguistic and Language Philosophy Perspective - Ahyati Kurniamala Niswariyana; Desak Made Yoniartini (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The language used in tourism promotion plays a strategic role in shaping tourists’ perceptions and experiences. However, the widespread use of persuasive language in tourism promotion has the potential to lead to the manipulation of meaning. This study aims to elucidate the forms of linguistic manipulation, as well as the cognitive and psychological mechanisms that render such strategies effective in influencing tourists’ perceptions and decision-making, whilst also examining their ethical implications. The study employed a qualitative method with a descriptive-analytical design through an interdisciplinary approach integrating forensic psycholinguistics and the philosophy of language. The data consisted of 5 tourism promotional texts collected from 3 digital platforms official tourism websites, Instagram, and Facebook promoting destinations in Lombok. The corpus was selected using purposive sampling based on the publication period (January 2024–June 2026), promotional purpose, audience engagement, and the presence of persuasive linguistic features. The data were analysed using an interactive analysis model involving data reduction, data display, and conclusion drawing. The research findings indicate that linguistic manipulations such as euphemisms, hyperbole, presuppositions, and framing are systematically employed to shape the image of a destination and influence tourists’ cognitive and affective processes via heuristic pathways. From a philosophy of language perspective, these practices reflect a non-neutral construction of meaning and have the potential to blur the boundaries between information and persuasion. The implications of this research underscore the importance of linguistic ethics in tourism promotion to maintain a balance between persuasive appeal and informational honesty.